DEPENDENSI DALAM MODEL RESIKO INDIVIDUAL UNTUK ASURANSI JIWA KELOMPOK - Pramesti, Getut; Kartiko, Sri Haryatmi (Journal of Mathematics and Mathematics Education, 2011)
ABSTRACT: TheÂ riskÂ dependenceÂ ofÂ anÂ insuranceÂ portfolioÂ inÂ aÂ groupÂ lifeÂ insuranceÂ canÂ beÂ describedÂ asÂ the individual risk model. It is used in modeling the claim distribution of insurance contracts over a fixed periodÂ ofÂ time.Â TheÂ distributionÂ computationÂ isÂ conductedÂ withÂ directÂ calculationÂ throughtÂ n convolution of individual claim distribution. We discuss the impact of the risk dependence on the net value of the stopâloss premium. A third risk factor in the dependence risk model is also introduced.Key words : The risk dependence, group life insurance, individual risk model, claim, the net value of the stop-loss premium.